2007
DOI: 10.1007/s11269-007-9200-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Hydropower Reservoir Operation Using Hybrid Genetic Algorithm and Chaos

Abstract: Genetic algorithms (GA) have been widely applied to solve water resources system optimization. With the increase of the complexity and the larger problem scale of water resources system, GAs are most frequently faced with the problems of premature convergence, slow iterations to reach the global optimal solution and getting stuck at a local optimum. A novel chaos genetic algorithm (CGA) based on the chaos optimization algorithm (COA) and genetic algorithm (GA), which makes use of the ergodicity and internal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(123 citation statements)
references
References 25 publications
2
115
0
2
Order By: Relevance
“…Chau et al (2005) employed the Genetic Algorithm based Artificial Neural Network (ANN-GA) and the Adaptive Network based Fuzzy Inference System (ANFIS), for flood forecasting in a reach of the Yangtze River in China. Similar studies are reported by Cheng et al ( , 2008a.…”
Section: Literature Reviewsupporting
confidence: 91%
“…Chau et al (2005) employed the Genetic Algorithm based Artificial Neural Network (ANN-GA) and the Adaptive Network based Fuzzy Inference System (ANFIS), for flood forecasting in a reach of the Yangtze River in China. Similar studies are reported by Cheng et al ( , 2008a.…”
Section: Literature Reviewsupporting
confidence: 91%
“…Therefore, the improved chaos logistic map is applied to frog population initialization to strengthen population diversity and distribution uniformity during the initialization process. It is beneficial to promote overall quality of initial population and locate feasible search zone effectively [53,54] Similarly, the chaotic sequence creation process is according to (17), and chaotic variables are mapped to feasible solution space of variable on the basis of (18). In IR-SFLA, variable is real coded, which denotes the power load in ELD subproblem and the frog position updating formula is in line with (14).…”
Section: Initial Population Based On Chaosmentioning
confidence: 99%
“…We do however acknowledge that other algorithms also exist as reviewed by Ahmad et al (2014). For instance, some papers consider a genetic algorithm (Hincal et al 2011;Cheng et al 2008) or a simulated annealing one (Teegavarapu and Simonovic 2002). Some papers also investigate multi-objective optimization rather than one objective function (Liao et al 2014;Kougias et al 2012).…”
Section: Hydropower Plant Managementmentioning
confidence: 99%